Simplified Diagnosis of Cardiovascular Autonomic Neuropathy in Type 2 Diabetes Using Ewing's Battery - Pafili, Kalliopi (Rev Diabet Stud, 2015)
AIM: To find a potential simplification of the established Ewing's battery for the diagnosis of cardiovascular autonomic neuropathy (CAN) in type 2 diabetes (T2D). METHODS: We included 152 patients (92 men) with mean age 64.51 ± 7.85 years and median diabetes duration of 12 years. Ewing's battery was used as the gold standard for the diagnosis of CAN. Against this, we compared the results from each test and their combinations. RESULTS: The 30:15 ratio exhibited the best diagnostic performance (AUC = 0.817, 95% CI: 0.730-0.903, p < 0.001), with 96% sensitivity, 65% specificity, and 94% negative predictive value (NPV). The corresponding values for the Valsalva ratio (VR) were 62%, 92%, and 85%, respectively. The 30:15 ratio was the strongest independent predictor of neuropathy in multivariate regression analysis; low levels yielded an odds ratio (OR) of 21.14 for CAN. The rise in diastolic blood pressure and the expiration/inspiration/VR ratio (E/I/VR) were also identified as independent predictors of CAN, with 9.45 and 10.79 ORs, respectively. CONCLUSIONS: The 30:15 ratio has the best diagnostic accuracy, primarily in the exclusion of CAN, by virtue of its very high sensitivity and NPV. If this ratio is positive for CAN, the VR, the rise in diastolic blood pressure, and the E/I/VR may be useful to increase diagnostic accuracy. This procedure is a simplified diagnostic approach that merits further evaluation to enable wider screening for CAN.